2013
DOI: 10.1007/s00464-013-3035-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of endoscopic submucosal tunnel dissection (ESTD) for surgical resection of esophageal leiomyoma

Abstract: ESTD is a safe and effective treatment for esophageal leiomyoma, with advantages over ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…Thus, submucosal injection of different solutions (such as glicerol or hyaluronic acid) a cushion beneath the lesion is created, separating the mucosa from the muscularis propia and enabling the tumor excision through a endoscopic submucosal dissection (ESD) (16,32), which safely allows enucleation of lesions that arise in the muscularis mucosae and the muscularis propia layer up to 3 cm. Endoscopic submucosal tunnel dissection (ESTD) has also been recently described, showing similar results and a lower risk of complications (27,28). We do not have enough experience in this kind of procedures, but we think they could be an available management alternative for experienced groups and small tumors, according to the published results (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, submucosal injection of different solutions (such as glicerol or hyaluronic acid) a cushion beneath the lesion is created, separating the mucosa from the muscularis propia and enabling the tumor excision through a endoscopic submucosal dissection (ESD) (16,32), which safely allows enucleation of lesions that arise in the muscularis mucosae and the muscularis propia layer up to 3 cm. Endoscopic submucosal tunnel dissection (ESTD) has also been recently described, showing similar results and a lower risk of complications (27,28). We do not have enough experience in this kind of procedures, but we think they could be an available management alternative for experienced groups and small tumors, according to the published results (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…To the best of our knowledge, there are no randomized, controlled trials comparing STER with other treatments of SMTs, but three retrospective studies have been published. (34) retrospectively assessed the clinical data of 39 patients with esophageal leiomyoma, 18 of which received STER and 21 of which received ESD, and demonstrated that the efficacy and complications of the two techniques were comparable, though STER was associated with decreased operating time and duration of hospital stay, and an increased rate of incision healing compared with ESD.…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…A 3-5 cm long submucosal tunnel functions as a good "leak-proof structure" and could reduce the potential risk of gastrointestinal tract leakage (air and/or fluid) and prevent secondary infection. Wang et al (29) demonstrated that STER has advantages over ESD in terms of promoting a rapid wound healing and reducing the operating time and hospital stay without compromising the success rate or increasing complications. With regard to SMTs > 10 mm, STER is the preferable choice compared with ESE with regard to the prevention of air leakage symptoms (30).…”
Section: Discussionmentioning
confidence: 99%